Anti-cysticercus antibody detection in saliva as a potential diagnostic tool for neurocysticercosis - Saha, Rumpa (Ann Indian Acad Neurol, 2016)
OBJECTIVES: This study was planned to determine the usefulness of anti-cysticercus IgG antibody detection in saliva for neurocysticercosis (NCC) diagnosis, along with serum C-reactive protein (CRP) level to serve as a surrogate marker. MATERIALS AND METHODS: In this prospective study of 14 months duration, blood and saliva samples were collected from 40 patients suspected to be suffering from NCC and were subjected to anti-cysticercus IgG antibody detection by ELISA. Serum CRP levels were estimated as acute-phase reactant by high sensitivity CRP ELISA. RESULTS: Anti-cysticercus IgG was detected in serum and saliva of 34 and 30 patients, respectively. Cases positive for salivary antibody were positive for serum antibody and their serum CRP level was higher than normal. Cases negative for salivary antibody had low serum CRP levels. Anti-cysticercus IgG detection in saliva was 88.24% sensitive, 100% specific, and had a positive predictive value of 100% and negative predictive value of 60%. Positive salivary anti-cysticercus IgG and high serum CRP level showed a significant association. Difference between CRP levels of patients positive for anti-cysticercus antibody in both serum and saliva, and patients positive for antibody in serum but not saliva was highly significant. CONCLUSIONS: Saliva, being painless and noninvasive, can be used as alternative to serum for NCC diagnosis.